MODEL PENILAIAN PENDIDIKAN KARAKTER OLEH GURU DI SMP BOARDING SCHOOL â€œPUTRA HARAPANâ€ PURWOKERTO - Istiana, Janatun (El-Hamra, 2019)
Abstract: The negative impact of globalization now makes Indonesian people forget the national character. The role of schools that work with families and communities is very much needed to instill strong character in children who are future leaders of the nation. In order to assess the results of implementing character education in schools, "PUTRA HARAPAN" SMP Boarding Scool Purwokerto carried out a 13-character assessment conducted by the teacher. This study aimed to find out "How the Character Education Assessment Model by Teachers in" PUTRA HARAPAN "Middle School Boarding School. The results show that the type of character education assessment currently used is a type of attitude assessment, while to help teachers assess using a variety of models, namely observation, total record, self evaluation and parenting. The implementation of the assessment is carried out in learning activities and activities outside the classroom. Furthermore, the condition of the teacher in the designation is directly involved in assessing, which also works with the guardians of students and students is an object of assessment following all activities. While the results of the assessment are reported on separate sheets in student learning outcomes (report cards). Key Words: Model, Assessment, Character Education